Exploring Homoeopathy And Thyroid Disorder Through Gnm Theory (Homoeopathy for All, 2026)
Thyroid disorders, including hy pothyroidism and hyperthyroid ism, constitute a major global health issue, influencing metabo lism, growth, and general well being. Worldwide, these disorders affect approximately 5–10% of the population, with a clear female pre dominance¹. Conventional medicine primarily attributes thyroid dysfunc tion to hormonal dysregulation, au toimmune mechanisms, and nutri tional or genetic factors. However, complementary medical systems broaden the perspective by consider ing psycho-emotional and systemic contributors to disease²˒⁴.
Keywords: Homoeopathy; German New Medicine; Thyroid Disorders; Hypothyroidism; Hyperthyroidism; Morsel Conflict; Holistic Health